2010
DOI: 10.1155/2010/716542
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Polymorphisms in Genes (AGT,MTHFR,GPIIIa, andGSTP1) Associated with Hypertension, Thrombophilia and Oxidative Stress in Mestizo and Amerindian Populations of México

Abstract: Several polymorphisms related to hypertension, thrombophilia, and oxidative stress has been associated with the development of cardiovascular disease. We analyzed the frequency of M235T angiotensinogen (AGT), A222V 5,10 methylenete-trahydrofolate reductase (MTHFR), L33P glycoprotein IIIa (GPIIIa), and I105V glutathione S-transferase P1 (GSTP1) polymorphisms in 285 individuals belonging to Mexican-Mestizo and five Amerindian population from México, by real time PCR allelic discrimination. Allele and genotype fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
8
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 0 publications
3
8
1
Order By: Relevance
“…Our observed MTHFR C677T frequencies were similar to those of populations with the same ancestry of the 1000GP or of previous reports (Davalos et al 2000; Juarez-Velazquez et al 2010; Wilcken et al 2003). Nevertheless, we have provided a more detailed description of within population differences that was not captured in any of the previous studies.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our observed MTHFR C677T frequencies were similar to those of populations with the same ancestry of the 1000GP or of previous reports (Davalos et al 2000; Juarez-Velazquez et al 2010; Wilcken et al 2003). Nevertheless, we have provided a more detailed description of within population differences that was not captured in any of the previous studies.…”
Section: Discussionsupporting
confidence: 92%
“…The risk-associated genotypes MTHFD1 1958AA and MTHFR 677TT had a particularly high frequency in the MEX population, 34 and 25 %, respectively. The frequencies of both SNPs in the AMI groups included in our study were >55 %, supporting the hypothesis that this phenomenon is related to the Amerindian ancestral contribution to the admixture process (Wilcken et al 2003; Davalos et al 2000; Juarez-Velazquez et al 2010). This is further supported by the observed gradient in the frequency of these variants in the MEX populations analyzed, within which, the highest and the lowest frequencies were observed in GUE and SON, the groups with, respectively, the highest and the lowest Amerindian ancestry contribution in this set of samples (Silva-Zolezzi et al 2009).…”
Section: Discussionsupporting
confidence: 86%
“…Consistent with this hypothesis, a previous study by our group showed that several Mexican Amerindian populations have the highest reported frequency of the 677T allele. 32 About the rs13306560 polymorphism, an extensive study with European nuclear families showed that this variant, located in the MTHFR/CLCN6 locus, is strongly associated with diastolic BP. 10 In this study, we found a risk association trend between the −23A allele and hypertension in the childhood population.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the fact that important ethnic differences have been observed in BMD and that the Amerindian-Mestizo population of Mexico are genetically heterogeneous (Canto-Cetina et al, 2013;Juárez-Velázquez et al, 2010), the principal aim of this study was to analyse the possible association between rs2228570 and rs731236 of VDR as well as their haplotypes, with variations in BMD in one Amerindian-Mestizo population from Mexico: post-menopausal Mayan-Mestizo women.…”
Section: Introductionmentioning
confidence: 99%